DAMPAK KEMAJUAN TEKNOLOGI PENDIDIKAN TERHADAP KINERJA GURU - Firmansyah, Firmansyah; Raupu, Sumardin; K., Nurdin; Herawati, Herawati (Kelola: Journal of Islamic Education Management, 2023)
The purpose of this study is to find out an overview of advances in educational technology at SMK Negeri 2 Palopo, an overview of teacher performance at SMK Negeri 2 Palopo, the impact of advances in educational technology on teacher performance at SMK Negeri 2 Palopo. This research uses descriptive research methods with a qualitative approach. The data collection techniques used are interviews and documentation. The subjects of this study consisted of the principal, the vice principal of the infrastructure section and the teacher council. The results of the study stated that advances in educational technology to teacher performance are very helpful because it makes it easier for teachers to access information and learning media easily. Advances in educational technology cannot be separated from positive impacts and negative impacts, positive impacts, namely being able to obtain information quickly, the emergence of learning methods. Educational technology also has a negative impact on teachers and students in schools, which can cause diversion of teacher functions, students can easily find information available on the internet, the confidentiality of test kits for education is increasingly threatened such as leakage of questions and others